Religion and Culture in the Preservation of Tembang Macapat in Jawa and Madura: A Historical Approach - Abdullah, A. Fatikhul Amin; El Rizaq, Agung Dwi Bahtiar; Oktafiana, Shinta; Rahman, Muhammad Hadiatur; Khairi, Ahmad Imam; Risdiana, Faraniena Yunaeni; Tianah, Itaanis; Azizah, Siti; Romadhon, Sahrul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Tembang Macapat (Macapat songs), as an expression of traditional oral literature, play an important role in preserving Islamic values in Java and Madura, making them a relevant material object in the context of culture-based da’wah. This research is important because it shows how local culture functions not only as an aesthetic heritage, but also as a spiritual and educational medium. The objective of this study is to examine the role of Tembang Macapat (macapat songs) as a medium for Islamic da’wah and moral education within the framework of local culture. This study employs a qualitative method with a historical-cultural approach, with the subjects of study comprising Tembang Macapat (macapat song) texts, Islamic manuscripts, and oral tradition narratives from Javanese and Madurese communities. The research findings reveal three main points: (1) Tembang (Songs) such as Pangkur, Dhandhanggula, and Megatruh contain Islamic values such as tazkiyatun nafs, tauhid, and awareness of the afterlife; (2) The Islamisation of culture occurs through symbolic and adaptive processes, not confrontational ones; (3) The Madurese song tradition conveys social ethics contextually within the family environment. These findings affirm that Tembang Macapat (macapat songs) are a strategic instrument in peacefully, aesthetically, and contextually grounding Islamic teachings within a multicultural society